THE DAILY CLASSROOM AS A SPACE FOR NARRATIVE SELF INSIDE OF CORAL SINGING LESSONS IN A SOCIAL PROJECT - Helena Doris Sala; Ana Lúcia Louro (Editora da Universidade de Santa Cruz do Sul, 2015)
This article shows a reflection on the teaching of music, highlighting issues related to social projects. The musical educator narrates their dilemmas, written between April 2010 and December 2012, as a teacher of choral singing for teenager in a social project, whose methodology "own narrative" and "self-narratives" (OLIVEIRA, 2009) that is reflected through the diaries of class (ZABALZA, 2004). The study aims to investigate the role of the teacher and the ways these in their teaching, using the tool of the daily class as a place to "write itself" and "narrative of oneself", promoting reflections in order to understand and modify their practices and thus shape their professional identity. The text also examines the conflicts present in practice in social projects (KATER, 2004; KLEBER, 2006, 2008;); questions the practice of choral singing (AMATO, 2007; TEIXEIRA, 2008), recounts classroom situations, focusing on professional identities involved in changing practices for achieving teenagers to class percussionists of choral singing.